Paciente masculino de 57 años con neumonía bacteriana. - Salazar Montes, Alfredo Josué (2021)
Pneumonia is a respiratory disease characterized by inflammation of alveolar sacs, it happens when a pathogenic microorganism (fungi, virus, or bacteria) reaches the lower respiratory tract. This disease is more prevalent in pediatric patients under 2 years old and in adult patients over 65 years old. The clinical characteristics of this pathology is dyspnea accompanied by fever, cough with expectoration, and crackling rales at the auscultation. The diagnosis of this pathology is made through the clinical picture presented by the patient, laboratory tests, etc., but this is confirmed by a chest X-ray, the chest X-ray is the gold standard in the diagnosis of pneumonia of any type. Treatment is initially empirical, but when the causative organism is isolated, a targeted treatment is initiated. The objective of this clinical case is to choose the appropriate treatment, as well as to prevent and identify risk factors for community-acquired pneumonia. The bibliographic research of scientific articles and works reviewed, as well as clinical guidelines were essential to obtain certified information. The methodology used was descriptive and qualitative.